Preventing Conflict Between Groups Through Multicultural Education In Elementary School - Kurniasari, Shanti; Desy Safitri; Sujarwo, Sujarwo (Council: Education Journal of Social Studies, 2024)
The goal of this essay is to examine how multicultural education is being implemented in Indonesia, particularly in elementary schools, as a possible preventative tool against conflicts between groups. This paper's author uses the literature study method, also known as literature study. The multiple publications and journals that were located served as the data sources, and repeated content analysis was the analysis method used. The results of this research indicate that while multicultural education has not been implemented properly in Indonesia, Durensewu I Elementary School's adoption of multicultural concepts has been considered successful. Furthermore, because students have been educated with the mindset of tolerance, respect, and awareness of differences between friendship groups, it could work as an approach to prevention